Osmanlı Döneminde Farsçadan Türkçeye Tercüme_x000D_ Edilen Bazı Mühim Tasavvufî Eserler_x000D_ - TOSUN, NECDET (My University, 2019)
Osmanlı döneminde birçok eser Farsçadan Türkçeye tercüme edilmiştir. Bu eserlerden önemli bir kısmı da tasavvuf konusundadır. Tercümeye konu olan Farsça eserlerden bazıları Anadolu (Türkiye) veMâverâünnehr (Özbekistan) gibi ana dilin Türkçe olduğu bölgelerde yazılmış, bazıları ise İran, Afganistan,Tacikistan ve Hindistan gibi ülkelerde kaleme alınmıştır. Bu Farsça eserler İslam dünyasında veya yazıldığıcoğrafyada beğenilip ilgi görmüş ve bu sebeple Anadolu’da Türkçeye tercüme edilmiştir. Bu tercümelerdenbazıları Osmanlı döneminde matbaada basılmış ise de, çoğunluğu yazma olarak kütüphanelerde durmaktadır. Bu tercüme eserlerden mühim olanları ve mütercimleri hakkında bu makalede bilgi verilmektedir.İran’da yazılan Bostan, Gülistân, Mantıku’t-tayr ve Pendnâme-i Attâr gibi eserler üzerine Osmanlı döneminde Türkçe birçok şerh yazılmıştır. Hattâ bu Türkçe şerhlerden bazıları çok değerli bulunmuş ve Farsçaya çevrilip yayınlanmıştır. Yani Farsçadan Türkçeye çevrilip şerh edilen eserler tekrar Farsçaya çevrilipasıl vatanında okunur hâle gelmiştir. Bu sayede ülkeler arasında kültür paylaşımı olmuş, İslam kültürüneönemli katkılar sağlanmıştır.Bu makâlede, Osmanlı döneminde Farsçadan Türkçeye tercüme edilen tasavvufî eserlerin önde gelenleritoplanıp bir araya getirilmiş, böylece konuya ilgi duyan kişilere ve araştırmacılara önemli bir kolaylıksağlanmıştır. Ayrıca makâlede, a) Osmanlı döneminde hangi tasavvufî eserlerin Türkçeye tercüme edildiği,b) Tercümelerin hangi coğrafyalardan (İran, Orta Asya, Hindistan vs.) yapıldığı, c) 15. Yüzyıldan sonratercümeye konu olan eserlerin İran’dan ziyâde Orta Asya ve Hindistan’a kaymasının sebepleri gibi problemlerin cevabı aranmıştır.

Many scholarly works were translated from Persian into Ottoman Turkish during the Ottoman period._x000D_ A considerable portion of those books was on Sufism. Some of these Persian works were written in_x000D_ regions where the native language was Turkish such as Asia Minor (Turkey) and Transoxiana (Uzbekistan), while others were written in other countries such as Persia, Afghanistan, Tajikistan and India._x000D_ These Persian works were appreciated and attracted attention in the Muslim world as well as in the_x000D_ lands where they had been written and thus they were translated into Turkish in Asia Minor. Even_x000D_ though some of these translations were published during the Ottoman period, most of them are maintained in the libraries as manuscripts. In this article, information will be given about the important ones_x000D_ of these translated works and their authors._x000D_ Many Turkish commentaries were written during the Ottoman Period on Sufi books such as Bostan,_x000D_ Gulistan, Mantıq al-tayr and Pand-i Attar which were written in Persia (Iran). Some of these Turkish_x000D_ commentaries were regarded so valuable that they were later translated into Persian and published. In_x000D_ other words, books which had been translated into Ottoman Turkish and commented upon were later_x000D_ re-translated into Persian and made available to the readers in their own land. In this way, they helped_x000D_ cultural exchange between countries and made significant contributions to Muslim culture._x000D_ In this article, some of the important Sufi works translated from Persian to Turkish during the Ottoman Period have been gathered. Thus, it aims to help the researchers and those who are interested in_x000D_ the subject. Moreover, the article seeks to answer certain questions such as, a) Which Sufi works were_x000D_ translated into Turkish during the Ottoman period, b) Where (Persia, Central Asia, India etc.) were these_x000D_ translations done? c) What were the reasons for the change of center of the works in question from_x000D_ Persia to Central Asia and India after the 15th century?
Some Important Sufi Works Translated from Persian into Turkish in the Ottoman Period